Phytochemical study of the alkaloid from the leaves of Catharanthus roseus G. Don (Family Apocynaceae) - Arquisola, Lucille F.
The study covers the extraction of the alkaloid from the leaves of Catharantus roseus G. Don (Fam. Apocynaceae) using the plant that bore violet flowers. The extraction of the alkaloid was done using a polar solvent, methanol and petroleum ether and phytochemical study was done on the petroleum ether extract using the thin layer chromatography melting point determination of the isolated crystals.